PENGARUH PELAYANAN ISLAMI DAN KUALITAS PRODUK TERHADAP LOYALITAS NASABAH BSI DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG KABUPATEN BANYUWANGI - Nur Anim Jauhariyah; Ulan Ani Setiawaty; Eko Budiywono (Jurnal Istiqro, 2023)
This study aims to analyze the effect of Islamic service and product quality partially and simultaneously on customer loyalty of Bank Syariah Indonesia (BSI) at Pondok Pesantren Darussalam Blokagung Banyuwangi. This type of research uses quantitative research with an explanatory research approach. The data source used is primary data in the form of result data from distributing questionnaires to Bank Syariah Indonesia (BSI) customers at Darussalam Islamic Boarding School Blokagung Banyuwangi. The sampling technique with purposive sampling was 50 students who became customers of Bank Syariah Indonesia (BSI). Data analysis used in this study is multiple linear regression analysis with the help of SPSS software. The results of multiple linear regression analysis show that 1) Islamic service quality partially has a significant effect on customer loyalty of Bank Syariah Indonesia (BSI) at Pondok Pesantren Darussalam Blokagung Banyuwangi; 2) Product quality partially has a significant effect on customer loyalty of Bank Syariah Indonesia (BSI) at Pondok Pesantren Darussalam Blokagung Banyuwangi; 3) Sharia service quality and product quality simultaneously have a positive and significant effect on customer loyalty of Bank Syariah Indonesia (BSI) at Pondok Pesantren Darussalam Blokagung Banyuwangi